2022
DOI: 10.1111/cid.13065
|View full text |Cite
|
Sign up to set email alerts
|

Association between industry support and the reporting of study outcomes in randomized clinical trials of dental implant research from the past 20 years

Abstract: Background: Industry support is a significant funding source in implant dentistry research, not only to provide regulatory processes, but also to validate and promote products through randomized clinical trials (RCTs). However, industry funding should not affect scientific outcomes. Purpose:The aim of this study was to investigate whether there is an association between industry support for RCTs in implant dentistry and a greater chance of the reporting of positive outcomes, and whether there are other funding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…A similar trend was observed by our research team, which found that randomized clinical trials performed by high-income countries were more likely to be funded by industry compared with upper- and lower-middle-income countries. 14 This result is consistent with all said in this discussion since high-income countries might provide better structural and financial conditions. In addition, most reputable and well-known dental implant companies were developed in USA and Switzerland, which certainly, favor more industry support directed to both countries (Website (2020).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A similar trend was observed by our research team, which found that randomized clinical trials performed by high-income countries were more likely to be funded by industry compared with upper- and lower-middle-income countries. 14 This result is consistent with all said in this discussion since high-income countries might provide better structural and financial conditions. In addition, most reputable and well-known dental implant companies were developed in USA and Switzerland, which certainly, favor more industry support directed to both countries (Website (2020).…”
Section: Discussionsupporting
confidence: 91%
“…The findings are consistent with a recent article from our research group that reported an increasing trend in collaboration between countries over the years in the dental implant field. 14 Previous study has also demonstrated a growth in scientific production linked to increased collaboration, mainly between high-income and upper-middle/lower-income countries. 19 Further reasons for overall collaboration include rising investments, easier access to financial resources, intellectual influences, increased scientific productivity, and exchange programs.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation